2018
DOI: 10.2147/dddt.s157109
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microRNA-146a in diabetic peripheral neuropathy through the regulation of inflammation

Abstract: PurposeRecent evidence has shown the involvement of inflammation in the development of diabetic peripheral neuropathy (DPN). MicroRNA-146a (miR-146a) is closely involved in the inflammatory response. However, the role of miR-146a in the inflammatory reaction in DPN has not been clarified. This study was designed to explore the role of miR-146a in the regulation of inflammatory responses in DPN.MethodsRats were randomly divided into three groups (n=6 per group): control group, type 2 diabetes mellitus (T2DM) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 34 publications
4
59
0
Order By: Relevance
“…Zhang et al, reported that miR-25 decreased reactive oxygen species content in diabetic peripheral nerves by activating NADPH oxidase and upregulating Advanced glycation endproduct (AGE)-RAGE interaction (50), In a diabetic state, reduced miR-146a expression was observed in serum, leukocytes, retina, heart, and PNS (65)(66)(67). MiR-146a was also reported to be involved in DN progression (64,68). Our recent experimental study adds substantially to this body of evidence (63).…”
Section: Mirnas and Inflammation Of Diabetic Neuropathysupporting
confidence: 54%
“…Zhang et al, reported that miR-25 decreased reactive oxygen species content in diabetic peripheral nerves by activating NADPH oxidase and upregulating Advanced glycation endproduct (AGE)-RAGE interaction (50), In a diabetic state, reduced miR-146a expression was observed in serum, leukocytes, retina, heart, and PNS (65)(66)(67). MiR-146a was also reported to be involved in DN progression (64,68). Our recent experimental study adds substantially to this body of evidence (63).…”
Section: Mirnas and Inflammation Of Diabetic Neuropathysupporting
confidence: 54%
“…Within this study, the CO-NPs were conjugated to microRNA with the goal to enhance the inflammatory response [159]. MiR-146a was chosen due to its reported ability to target adapter molecules of the NF-κB pathway, resulting in increased IL-6 and IL-8 gene expression [160][161][162]. The authors could show that CO-NP or miR146a treatment alone did not have an effect on the healing rate compared to the saline control in both mouse and pig diabetic wound-healing models.…”
Section: Wound Healingmentioning
confidence: 99%
“…miRNA-146a plays a role in diabetic peripheral neuropathy [ 55 , 56 ]. miRNA-146a in sciatic nerve tissue was attenuated in mice with type 2 diabetes and miRNA-146a levels in plasma and sciatic nerve tissue were enhanced following administration of miRNA-146a mimics in diabetic mice.…”
Section: Micrornas In Peripheral Neuropathymentioning
confidence: 99%